Membedah Karya Erica Hestuwahyuni Melalui Studi Bahasa Rupa - Kurniawati Gautama (JURNAL RUPA, 2017)
Bahasa Rupa (picture-writing) is an invention of Prof.Dr. Primadi Tabrani to analize the specific character of Eastern tradition which is different from Western. It is a visual communication study in modern and traditional picture-writing system. The modern (western) bahasa rupa uses ‘close up’ format which recognized universally, whereas the traditional (eastern) system such as the relief of Borobudur Temple, Wayang Beber (scroll-painted picture presentations), Balinesse Painting, have specific drawing technique. This essay, will analize an Indonesian and international recognized female painter, Erica Hestuwahyuni, whose artworks show childlike character. As introduction this essay will elaborate the differences between painting and drawing, also Bahasa Rupa theory and character of children drawings.